TRADITIONS AND INNOVATIONS IN ISSA BOTASHEV'S CREATIVE WORKS - А. M. SARBASHEVA (Кавказология)
The article examines the works of the Balkar writer, patriarch of stage literature Issa Botashev (1925-1991). Research attention is focused on the dramatic works of the artist of the word ("Dawn in the Mountains", "The Fate of Soltan", "Abrek", "At Dawn", "The Feat of the Mountain Woman"), since drama is central to his spiritual heritage. A special merit of the writer is that he is the founder of historical documentary drama in Balkar literature. The specificity of the dramatist's artistic understanding of the historical era, the reconstruction of past events from the point of view of aesthetic and cognitive motivations is noted. It becomes obvious From the analysis, that the author's creative attempt to overcome the stereotypical thinking that prevailed at the previous stages of the development of national literature, expressed in the alternative principle of creating characters, passion for the socio-historical background to the detriment of the study of the inner world of the characters, the cliched perception of reality, etc. tendencies (polyphonism of conflite lines, defining the moral essence of a hero in conditions of class confrontation, synthesis of documentary and fiction, updating the system of images) that characterize the originality of the writer's thinking, the depth and breadth of the author's position in solving complex aesthetic problems. The study showed that Issa Botashev made positive adjustments to the process of revival and actualization of the dramatic direction in Balkar literature in the second half of the 20th century. The main research methods are historical, biographical and typological.